Indicator Models of Real GDP Growth in Selected OECD Countries - Sédillot, Franck (OECD Publishing, 2003)
Accurate and timely information on the current state of economic activity is an important requirement for the policymaking process. Delays in the publication of official statistics mean that a complete picture of economic developments within a particular period emerges only some time after that period has elapsed. The research described in this paper develops a set of econometric models that provide estimates of GDP growth for a number of major OECD countries and zones in the two quarters following the last quarter for which official data have been published. These models exploit the considerable amount of monthly conjunctural information that becomes available before the release of official national accounts data. Information is incorporated from both 'soft' indicators, such as business surveys, and 'hard' indicators, such as industrial production and retail sales, and use is made of different frequencies of data and a variety of estimation techniques. An automated procedure is ...
Keywords: Economics